Global burden of esophageal diseases: a comprehensive analysis of disease trends and risk factors from 1990 to 2021 - Yanbin Wei; Endian Liu; Jiafei Peng; Yanqing Liu; Xiujing Sun; Xin Yao (BMC Gastroenterology)
Abstract Background Esophageal diseases (ED) are a common category of upper gastrointestinal disorders, mainly including gastroesophageal reflux disease (GERD), esophagitis, Barrett’s esophagus, achalasia, and esophageal cancer (EC). In recent years, the high recurrence rate of GERD and poor prognosis of EC are paid more attention, collectively contributing to the global burden of ED. Methods For this study, we systematically analyzed the global distribution of ED from 1990 to 2021, detailing the burden across different countries, regions, and socio-demographic index (SDI) levels. Furthermore, we explored temporal trends in ED burden over this period and conducted decomposition analysis, health inequality analysis, and frontier analysis. Finally, we projected trends in ED burden from 2022 to 2045, and quantify contributions of associated risk factors to disability-adjusted life years (DALYs) of EC. Results The absolute numbers of incidence, mortality, and DALYs for GERD and EC showed increasing trends from 1990 to 2021, while their age-standardized rates (ASRs) demonstrated divergent patterns: stable for GERD and declining for EC. The highest ASRs were observed in low-middle SDI regions for GERD and high-middle SDI regions for EC, respectively, with population as a main driver. If current trends continue, the burden of GERD will continue to rise, whereas that of EC will persistently decline by 2045. In 2021, DALYs of EC were mainly attributed to smoking (36.5%) and alcohol use (16.2%). Conclusions For GERD and EC, the global burden continued to rise and decline from 1990 to 2021, respectively. Developing targeted public health strategies in different countries and regions is crucial for alleviating the global burden of ED.